P150 Hospital Re-admissions With Exacerbation Of Obstructive Pulmonary Disease In Illicit Drug Smokers. (10th November 2014) - Yadavilli, R; Huang, R; Collins, AM; Ding, W Yew; Garner, N; Williams, J; Burhan, H
Abstract : Introduction: Patients with obstructive pulmonary disease (asthma or chronic obstructive pulmonary disease – COPD) who smoke illicit drugs are at an increased risk of hospital admissions. We compared hospital re-admission rates due to exacerbations of obstructive pulmonary disease amongst current/ex-illicit drug smokers versus current/ex-tobacco smokers. Hypothesis 'Are those who smoke illicit drugs admitted to hospital with a clinical diagnosis of exacerbation of COPD more likely to be re-admitted with a further exacerbation than current/ex-tobacco smokers?' Methods: Re-admission was defined as any admission, after the first, with an exacerbation of obstructive pulmonary disease during the study period. All admissions with a presumptive diagnosis of 'exacerbation of COPD' between January 2009 and September 2011 were reviewed. This was performed retrospectively using our COPD admission database. Results: There were 950 sequential hospital admissions in 709 patients over a 33 month period. We found 250 ex-tobacco smokers, 370 current tobacco smokers and 89 current or ex-illicit drug smokers. Re-admission rates with exacerbation of obstructive pulmonary disease were higher in illicit drug smokers compared to current/ex-tobacco smokers (1.00 v. 0.22/0.26, p < 0.001). Illicit drug smokers were younger (50 v. 72.9/69.9 [mean 71.2] years, p < 0.001) and had shorter length of hospital stay (7.44 v. 9.28/10.69 [mean 9.87] days, p = 0.038). Illicit drug smokers with FEV1 < 1 litre (L) had higher readmissions (2.56) than ex/current tobacco smokers (0.6) with FEV1 < 1L (p < 0.001) [Table 1 ]. Illicit drug smokers with FEV1 > 1L did not show this trend (p = 0.236). Tobacco pack years were higher in tobacco smokers (40.22) compared to illicit drug smokers (22.47), p. Admissions requiring non-invasive ventilation (NIV) for type 2 respiratory failure were more common in illicit drug smokers (8.4 v. 3%, p < 0.002). Conclusion: We have shown that readmission rates in illicit drug smokers are higher than in tobacco smokers. These patients tend to be younger, have a male predominance, have shorter length of hospital stay and are more likely to require NIV; readmissions were more predominant in illicit drug smokers with an FEV1 1.